Konserwacja dwustronnego obrazu Andrzeja Wróblewskiego – pokora i wyzwanie - Markowski, Dariusz (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2016)
The paper analyses the conservation issues of the two-side painting by Andrzej Wróblewski Dworzec na Ziemiach Odzyskanych /Treść uczuciowa rewolucji from the National Museum in Poznań. The treatment of the significant two-side painting was a challenge. Works conducted in 2011 were related both to verso but especially to the seldom exhibited recto of the painting. The backside image was a part of the bigger composition – Treść uczuciowa revolucji (The emotional content of the revolution), executed in 1948. It was cut into halves by the painter him-self and used for another paintings. Wróblewski and most important phases of his art as well as the history of the restored painting are presented. Subsequently the technique of the painting, condition and reasons of deterioration as well as conservation treatment enabling exhibiting of restored recto are discussed.